Love is blind: Partisan alignment and political corruption in Spain - Miguel Ángel Borrella Mas; Martin Rode (SERIEs - Journal of the Spanish Economic Association, 2021)
Ever since the spectacular boom and bust cycle of the Spanish real estate industry, endemic corruption at the local level has become a widely recognized problem in the national public discourse. In an effort to expose an under-explored political determinant, this paper investigates the effect of local and regional alignment in fomenting corruption at the Spanish municipal level. To do so, we construct an ample panel dataset on the prevalence of corrupt practices by local politicians, which is employed to test the possible impact of partisan alignment in three consecutive joint municipal and regional elections. Findings show aligned municipalities to be more corrupt than non-aligned ones, an effect that is further associated with absolute majorities at both levels of government and higher capital transfers. By contrast, we also show that "throwing the rascals out" could be an effective strategy for curbing the corrupt practices of aligned municipalities. This indicates that the democratic political process may be effective in corruption control if agreements can be reached to remove corrupt politicians or parties from power.
Keywords: D72; D73; H77; P16; 330; Corruption control; Elections; Partisan alignment; Political corruption; Spain